Patient reported outcome measures (PROMS) – 30-day mortality and adverse events post colonoscopy: A prospective observational study from a metropolitan Australian hospital. (2020) - Khaing, Myat Myat; Kellar, Petrina; Hartnell, Felicity; Croese, John; Hodgson, Ruth; James, Thomas; Franz, Robert; Hughes, Andrew; Shaw, Ian; Iswariah, Harish; Vandeleur, Ann; Rahman, Tony
No abstract available